An investigation of intrinsic and extrinsic motivation on towards the level of employees' job satisfaction at Pejabat Daerah Kota Tinggi (PDKT), Johor Darul Takzim / Norhidayah Hamdan - Hamdan, Norhidayah (Faculty Of Business Management, 2016)
The study was conducted in order to identify the relationship between motivation and the level of employees' job satisfaction. This study was to investigate whether job satisfaction were influenced by intrinsic or extrinsic motivation. The sample that was investigated consisted from the staffs of Pejabat Daerah Kota Tinggi (PDKT). The instrument used to conduct this survey was by distributing the questionnaires to respondents and simple random sampling have been chosen as a technique. The findings of this study was analyzed and calculated by using IBM SPSS version 21.0 in order to identify the level motivation variables of employees and the relationship between types of motivation and the level of employees' job satisfaction. The result shows the mean values of each motivation variables and Pe8lSQn Product-Moment Correlation Coefficient was used to measure the strengths of variables which resulted the level of employees' job satisfaction at Pejabat Daerah Kota Tinggi (PDKT) was influenced by extrinsic motivation instead of intrinsic motivation. This showed that employees were lack of self-interest on motivating themselves towards their job satisfaction. Therefore, praised and trusted were suggested as recommendation for organization on increasing employee self motivation towards job satisfaction.